Novel escape mutants suggest an extensive TRIM5α binding site spanning the entire outer surface of the murine leukemia virus capsid protein. - Sadayuki Ohkura (Public Library of Science (PLoS), 2011)
After entry into target cells, retroviruses encounter the host restriction factors such as Fv1 and TRIM5α. While it is clear that these factors target retrovirus capsid proteins (CA), recognition remains poorly defined in the absence of structural information. To better understand the binding interaction between TRIM5α and CA, we selected a panel of novel N-tropic murine leukaemia virus (N-MLV) escape mutants by a serial passage of replication competent N-MLV in rhesus macaque TRIM5α (rhTRIM5α)-positive cells using a small percentage of unrestricted cells to allow multiple rounds of virus replication. The newly identified mutations, many of which involve changes in charge, are distributed over the outer 'top' surface of N-MLV CA, including the N-terminal β-hairpin, and map up to 29 A(o) apart. Biological characterisation with a number of restriction factors revealed that only one of the new mutations affects restriction by human TRIM5α, indicating significant differences in the binding interaction between N-MLV and the two TRIM5αs, whereas three of the mutations result in dual sensitivity to Fv1(n) and Fv1(b). Structural studies of two mutants show that no major changes in the overall CA conformation are associated with escape from restriction. We conclude that interactions involving much, if not all, of the surface of CA are vital for TRIM5α binding.